Italian validation of the DEMQOL-PROXY: Exploratory Factor Analysis, Convergent and Divergent Validity: Exploratory Factor Analysis, Convergent and Divergent Validity of Italian version of the DEMQOL-PROXY - Miraglia Raineri, Alessandra; Bonfigliuoli, Chiara; Guasconi, Massimo; Camaiani, Francesca; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. we present in this paper a complete Italian validation version. We show some psychometric properties of the Italian version of the DEMQOL-PROXY: Structural validity (by use Exploratory Factor Analysis), convergent validity and divergent validity in Italian language Method.We enrolled a sample of 182 caregivers of people with mild to moderate Dementia. In particular, we collected 90 questionnaires of professional caregivers and 92 questionnaires of family caregivers. We used Exploratory Factor Analysis (Varimax rotation), to identify the saturation of items on the relevant factors.The internal consistency of the instrument was evaluated by using the Cronbach Alpha coefficient. Finally, referring to the Validity of convergent and Divergent validity, we used Spearman’s correlation coefficient by comparing the various instruments of the study. Results. Our result shows that the variance explained by 4 factors corresponds to almost 51% of the total variance. Factors extracted in our Italian version are: Cognition;Negative and Positive emotion; Daily activity and Membership. Conclusion. The Italian version of the DEMQOL-PROXY point out very good psychometric properties: factors extracted are similar to the original version and convergent and divergent validity show good proprieties. We consider this paper as a complete Italian Validation.